Analisis Hak Asuh Anak Dalam Putusan Pengadilan Agama Lahat Nomor 685/Pdt.G/2022/PA.LT: Perspektif Maqâsid Al-Syarî’ah Muhammad Thâhir Ibn Âsyûr - Bagus Ary Darmawan; M. Reza Saputra; Jaenal Aripin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Marriage is an important event where humans, as social beings, need partners to fulfill their life needs. In marriage, legal standards are necessary to regulate the family's rights, obligations, and responsibilities to build a happy and prosperous family. Every married couple aspires to have offspring, which is considered a trust from Allah SWT. This research aims to provide a deep understanding of the implementation of maqasid syariah in court decisions related to child custody post-divorce, which is expected to serve as a reference for legal practitioners and academics. A qualitative approach with a case study method was used to analyze the decision of the Lahat Religious Court Number 685/Pdt.G/2022/PA.LT, with data obtained through court decision documentation and literature related to maqasid syariah and Islamic law. The analysis was conducted in the context of the principles of maqasid syariah, especially the aspects of hifz al-nafs (preservation of life) and hifz al-nasl (preservation of lineage). The results of the study show that the judge granted custody to the father because the mother was deemed unable to provide adequate care. The judge's considerations align with the principles of maqasid syariah, which emphasize the importance of the child's physical and mental well-being. The research concludes that the principles of maqasid al-syariah can be applied in the modern judicial system to ensure the child's best interests in custody cases, demonstrating that the welfare and safety of the child must be the primary priority in any legal decision.